INFLUENCE OF Morinda citrifolia, L. FRUIT EXTRACT AS ADJUVANT ON IG-Y PRODUCTION RAISED IN LAYING CHICKENS AGAINST AVIAN INFLUENZA VACCINE - Ediati Sasmito; Sri Harimurti; Hendy Nurhidayat; Wahyu Anggoro; Elika Nur Hikmawati; Joko Tri Wibowo; Atut Sulma Avi; Nurul Hilmi (Indonesian Journal of Pharmacy, 2012)
Immunized avian with vaccine, produces specific antibody in the serum as well as in the egg yolk. An adjuvant is used to augment  the   effects  of  a  vaccine  by  stimulating  the  immune response.   Morinda  citrifolia,  L.,  especially  the  fruit  contains  of some  chemical  compounds  such  as  polysaccharide,  scopoletin, damnacanthal,  proxeronine  and  proxeroninase.  All  those  of active  compounds,  are  soluble  in  different  solvents  and  have different  activities.  Some  of  those  compounds  have  adjuvant activity.  The  aim  of  our  study  was  to  observe  the  capability  of M.citrifolia  fruit  extracts  as  adjuvant  to  enhance  the  specific antibody  (IgY)  production  in  immunized  laying  chickens Lohmann  strain  (28  weeks  old)  with  a  commercially  available avian  influenza  (H5N2)  vaccine.  To  the  groups  (@6)  of  laying chickens  were  orally  administered  once  a  day,  through  out  of the  study,  with   n-hexane  (group  I;  divided  ino  3  sub  groups), ethanolic  (group  II;  divided  into  3  subgroups)  and  aqueous extract  (group  III;  divided  into  3  subgroups)  of  M.citrifolia (prepared  in  capsules)  on  dose  of   29  mg;  58  mg;  and  116 mg/chicken/day,  respectively,  and  group  IV  as  plasebo  control and  group  V  as  normal  control.  All  of  the  groups  were  induced with avian influenza vaccine, except the normal control. Eggs of 3, 6, and 10 weeks after immunized, were collected. Isolation of IgY  was  performed  by  repeated  polyethylene  glycol  6000 precipitation steps. IgY obtained was analyzed by indirect ELISA  method.  The  serum  was  tested   for  antibody  specificity  against the  influenza  H5N2  virus  by  hemagglutination-inhibition  (HI) method.  The  result  of  this  study  showed  that  the  dose  of  58 mg/chicken/day  of  aqueous  extract  of  M.citrifolia  fruit  had  an optimal  capability  to  enhance  specific  antibody  (IgY)  as  well  as IgG serum production against avian influenza (H5N2) vaccine .Key  words:  Adjuvant,  extract,  Morinda  citrifolia,  L.,  H5N2  vaccine, immunoglobulin yolk (IgY)